A citrus essential oil causes higher disturbance on the growth kinetics of Enterococcus faecalis than Lactobacillus rhamnosus - Ambrosio, Carmen M. S. (2022)
Essential oils (EOs) have turned a promising alternative to using antibiotics in poultry production due to their antimicrobial properties. EOs could effectively combat pathogenic bacteria affecting poultry. Particularly, Citrus EOs, a by-product of citrus processing industries, could be a feasible alternative to this end due to their vast availability in the global market. Enterococci are associated with intestinal and extra-intestinal infections in poultry, which can increase poultry mortality. On the other hand, Lactobacilli are beneficial bacteria inhabiting the poultry gut and have health-promoting effects. The aim of this study was to evaluate the antibacterial activity of a commercial citrus EO, Orange oil phase essence (OOPE), on Enterococcus faecalis and Lactobacillus rhamnosus as well as to determine OOPE chemical composition. Results showed that OOPE inhibited E. faecalis and L. rhamnosus at 14.8 mg/mL. However, the evaluation of OOPE effects on the growth kinetics parameters of both bacteria reveled that OOPE caused higher disturbances on the growth kinetics of E. faecalis than L. rhamnosus. OOPE significantly reduced the maximal culture density (A) and growth rate (µmax) and extended the lag phase duration (λ) of E. faecalis in a dose-dependent manner, while OOPE slightly extended λ and affected µmax of L. rhamnosus. OOPE at 3.70 mg/mL reduced A and µmax in ~87.34 and 90.2%, respectively, while increased λ 3.8 times of E. faecalis. OOPE at this concentration reduced µmax in 11.8% and extended λ 1.38 times of L. rhamnosus. Therefore, OOPE had a selective antibacterial activity, presenting higher activity on E. faecalis. Despite, limonene was identified as the major compound (87.22%) of OOPE, minor compounds such as trans-carveol could be involved in conferring the selective antibacterial activity of OOPE.